Preliminarily analysis of carbamazepine (cbz) c 0 in patients visited Isfahan epileptic clinics - Zahra Tolou-Ghamari (International Journal of Preventive Medicine, 2013)
Background: Carbamazepine (CBZ) is mostly considered as the first line of effective treatment against simple or complex partial seizure and primary-secondary generalization. To prevent side-effects related to higher amount of CBZ minimum concentration (C 0 ) in body fluid or seizure attacks associated to lower amount of CBZ-C 0 , the suggested minimum therapeutic concentrations range from 4 to 12 ng/ml (according to previous publications). The aim of this preliminarily study was to investigate the scope of discrepancy associated to the C 0 of CBZ in patients visited Isfahan Epileptic Clinic. Methods: A cross-sectional study of 22 patients located in neurology ward of Isfahan Neurosciences Research Centre (INRC) was carried out between April 1, 2012 and December 31, 2012. Female (n = 9) and male subjects (n = 13) with a mean age of 27.4 years (range; 16-38 years) were studied. Pharmacological (CBZ-C 0 ) and demographical variables were recorded and processed in excel. Results: The results of CBZ-C 0 showed wide inter-individual variability. The mean value of CBZ-C 0 was 7.2 ng/ml. In 10 out of 22 patients, CBZ-C 0 were lower than the suggested therapeutic window (4-12 ng/ml). CBZ-C 0 in nine patients was non-detectable and in one patient was 0.5 ng/ml (45% <4 ng/ml). In 55% of the patients, CBZ-C 0 ranged from 4.8 to 12 ng/ml. Conclusions: A schedule therapeutic drug monitoring based on measurement of CBZ-C 0 for individual patient could be a practical marker to achieve therapeutic objectives. Further study related to correlating of CBZC 0 to clinical events in Iranian Epileptic population seems to be valuable.